Impact of mindfulness training and yoga on injury and pain-related impairment: a group randomized trial in basic combat training - Smith, Carl D.; Gutierrez, Ian A.; Nassif, Thomas H.; Jordan, Kimberley L.; Taylor, Kathryn M.; Jha, Amishi P.; Adler, Amy B. (Frontiers in Psychology, 2023)
Introduction: Service members are at risk for pain-related difficulties in functioning and physical injury. Previous studies suggest that mindfulness training (MT) and yoga may prevent these outcomes. The present study was designed to determine the impact of MT and yoga on the health, pain, and injury of Army trainees completing ten weeks of basic combat training (BCT).Methods: Platoons (≈ 40 trainees per platoon) were randomized to MT and yoga or training-as-usual in October to December 2020 at a large installation in the US. Self-reported outcomes were health, pain level, and pain impact on training, sleep, mood, and stress. Objective outcomes were injuryrelated medical encounters and number of diagnoses. The trial was registered at ClinicalTrials.Gov (NCT05550610).Results: Intervention trainees reported significantly better health (OR = 1.05, 95% CI [1.00, 1.10]) and less impact of pain on training (OR = 0.81, 95% CI [0.74, 0.90]), sleep (OR = 0.88, 95% CI [0.81, 0.95]), mood (OR = 0.86, 95% CI [0.78, 0.96]), and stress (OR = 0.88, 95% CI [0.79, 0.98]). There was no significant difference in injury-related medical encounters (AOR = 0.70, 95% CI [0.48, 1.03]), but intervention trainees had fewer diagnoses (OR = 0.67, 95% CI [0.47, 0.95]) and were 30% less likely to have a first medical encounter at any time during BCT. This difference emerged three weeks into BCT.Discussion: A combined MT and yoga intervention resulted in better trainee health. The US Army and other organizations requiring resilience under extreme stress should consider implementing MT and yoga to offset risks to employee health.